COVID-19 vaccination strategy for hospital staff in Germany: a cross-sectional study in March–April 2021. (August 2022) - Mardiko, A.A.; Heinemann, S.; Bludau, A.; Kaba, H.E.J.; Leha, A.; von Maltzahn, N.; Mutters, N.T.; Leistner, R.; Mattner, F.; Scheithauer, S.
Summary: Background: SARS-CoV-2 vaccination for healthcare workers (HCWs) started in Germany in December 2020. Hospitals had little time to prepare a vaccination strategy. Aim: To gather information on the initial vaccination strategy for HCWs from the infection control practitioners in Germany. Methods: A cross-sectional, ethically approved questionnaire was developed, formatted as an online survey and pre-tested. Infection control practitioners responsible for hygiene/infection prevention in 987 randomly selected German hospitals were invited to participate in the survey in March and April 2021. For statistical analysis, the hospitals were categorized into two groups based on bed capacity (<500 beds: small; ≥500 beds: large). Findings: One hundred out of 987 (10%) infection control practitioners completed the survey. In 80% of the participating hospitals, HCW vaccination prioritization was based on recommendations of the German standing committee on vaccination (STIKO). Even so, only 54% prioritized the vaccination of HCWs with contact to vulnerable patients, thus deviating from STIKO recommendations. HCWs with a high personal health risk were prioritized for vaccination in 24% of the hospitals. Transferring unvaccinated HCWs to an area with less infection risk was considered by 2% of large and 12% of small hospitals. Conclusion: Vaccination prioritization differed across hospitals and deviated from STIKO recommendations. A pandemic preparedness concept should address the potential impact of divergent strategies compared to a common approach. In addition, further studies analysing the reasons why HCWs remain unvaccinated are needed to adopt effective strategies. This is especially important against the background of facility-based compulsory vaccination.